Supply chain relationships in circular business models: Supplier tactics at royal SMIT transformers - Marlies van Tilburg; Harold Krikke; Wim Lambrechts (Logistics, 2022)
Background: Despite growing popularity, Circular Economy has not reached its full potential. One of the frequently mentioned success factors is the adoption of a Circular Business Model. However, fueled by (too) many constraints, its implementation is often hampered by so-called vicious cycles. Successful Circular Business Models require intensive collaboration between buyers and suppliers, with one of the key questions remaining who takes the initiative and leads the development: buyer or supplier? Methods: Through a single case study combining desk research, interviews, participative observations and analysis of vicious cycles, we investigate how supply chain relationships managed by the supplier can enhance the implementation of Circular Business Models. Results: We show that supplier tactics can relax constraints and break vicious cycles through (1) buyer-supplier relationship management, (2) functional integration of stakeholders and (3) incentive management. We also show that, due to supplier captive conditions, a number of enabling factors are indispensable, namely: (1) the availability of buyer incentives; (2) (joint experimenting to develop) circular knowledge; (3) sharing clear visions on circularity; (4) being transparent in possibilities; and (5) supply chain leadership. Conclusions: As a consequence, strategic trust-based partnerships are a prerequisite for turning vicious cycles into virtuous cycles. Future research should also investigate the role of the buyer, including buyer captive conditions, and how to shape supply chain leadership. Finally, the role of supplier tactics in relation to other success factors next to Circular Business Models needs to be further explored.
Keywords: 650; circular business models; circular economy; closed-loop supply chains; supplier tactics; supply chain relationships